Application of landsat images for quantifying the energy balance under conditions of land use changes in the semi-arid region of Brazil - Teixeira, Antônio H. de C.; Hernandez, Fernando B. T. [UNESP]; Lopes, Hélio L. (SPIE, the international society for optics and photonics, 2012)
In the Nilo Coelho irrigation scheme, Brazil, the natural vegetation has been replaced by irrigated agriculture, bringing importance for the quantification of the effects on the energy exchanges between the mixed vegetated surfaces and the lower atmosphere. Landsat satellite images and agro-meteorological stations from 1992 to 2011 were used together, for modelling these exchanges. Surface albedo (α0), NDVI and surface temperature (T0) were the basic remote sensing retrieving parameters necessary to calculate the latent heat flux (λE) and the surface resistance to evapotranspiration (rs) on a large scale. The daily net radiation (Rn) was obtained from α0, air temperature (Ta) and short-wave transmissivity (τsw) throughout the slob equation, allowing the quantification of the daily sensible heat flux (H) by residual in the energy balance equation. With a threshold value for rs, it was possible to separate the energy fluxes from crops and natural vegetation. The averaged fractions of Rn partitioned as H and λE, were in average 39 and 67%, respectively. It was observed an increase of the energy used for the evapotranspiration process inside irrigated areas from 51% in 1992 to 80% in 2011, with the ratio λE/Rn presenting an increase of 3 % per year. The tools and models applied in the current research, can subsidize the monitoring of the coupled climate and land use changes effects in irrigation perimeters, being valuable when aiming the sustainability of the irrigated agriculture in the future, avoiding conflicts among different water users. © 2012 SPIE.
Keywords: Latent heat flux; NDVI; Sensible heat flux; Surface albedo; Surface resistance; Surface temperature; Energy balance equations; Irrigated agriculture; Irrigation schemes; LANDSAT satellite images; Surface temperatures; Arid regions; Atmospheric temperature; Climate models; Ecosystems; Energy balance; Evapotranspiration; Hydrology; Irrigation; Land use; Latent heat; Remote sensing; Satellite imagery; Solar radiation; Surface properties; Vegetation; Water supply; Heat flux